The influences of water quality on fish occurrences in Kuala Mai, Pahang River and Ulu Tembeling, Tembeling River, Pahang, Malaysia - Mohd Sukeri, Nur Farhanim; Abd. Rashid, Zulkafli; Saba, Abdulwakil Olawale; Abdullah Halim, Muhammad Rasul; Azmai, Mohammad Noor Amal (Universiti Putra Malaysia Press, 2020)
This study assessed the fish community structures and influences of water quality on fish occurrences in Pahang and Tembeling rivers, Pahang. Fish samplings and water quality measurements were conducted in Kuala Mai, Pahang River and Ulu Tembeling, Tembeling River from 12 and eight different sampling points, from October 2007 to September 2008, and August 2006 to August 2007, respectively. The fish diversity, richness and evenness indices were determined, while the water quality parameters were compared for both rivers. Multivariate analyses were then used to explore the effects of water physicochemical parameters on the fish occurrences. A total of 2,391 individuals were collected from this study, comprising of 20 families and 65 species of fish. Using the gill nets, cast nets and fishing rods, a total of 55 fish species from 17 families were recorded in Kuala Mai, Pahang River, compared to 47 species from 15 families in Ulu Tembeling, Tembeling River. There were significant differences (p < 0.05) for fish diversity (H and 1-D), but not for fish evenness (e) and richness (D) between both rivers. The mean water temperature, ammonia nitrogen and total suspended solids were significantly different (p < 0.05) in both rivers. Apart from the influences of pH, alkalinity and phosphate in both rivers, the results showed that the temperature, dissolved oxygen and conductivity were the major influencers on the fish occurrences in Kuala Mai, Pahang River, while ammonia nitrogen and total suspended solids in Ulu Tembeling, Tembeling River. Fish conservation and stock management efforts are urgently needed due to the decreasing number of near-threatened, endangered and critically endangered fish species in both rivers.